1999
DOI: 10.1207/s15324826an0604_5
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Age and Gender on the Perception of Lexical Emotion

Abstract: The primary purpose of this study was to examine the perception of lexical/verbal emotion across the adult life span. Secondary goals were to examine the contribution of gender and valence (i.e., pleasantness/unpleasantness) to the processing of lexical emotional stimuli. Participants were 28 young (ages 20-39), 28 middle-aged (ages 40-59), and 28 older (ages 60-85) right-handed adults; there were 14 men and 14 women in each age group. Age groups were comparable on demographic and cognitive variables. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 50 publications
7
39
0
Order By: Relevance
“…The precise reason for this pattern of results is unclear, although such results are possibly attributable to the basal effect of the verbal nature of the stimuli, as was specified by Ali and Cimino. Relatedly, Grunwald et al (1999) suggested that studies in which the perception of emotional words has been examined (i.e., lateralized paradigms, such as tachistoscopic techniques) have been less conclusive with regard to hemispheric specialization for emotion than have paradigms in which facial emotion or emotional prosody has been examined (for a review, see Borod, Bloom, & Haywood, 1998). The reason(s) for the inconclusiveness are poorly understood, although they may be attributable in part to similar weaknesses in experimental design, as described below.…”
Section: Discussionmentioning
confidence: 99%
“…The precise reason for this pattern of results is unclear, although such results are possibly attributable to the basal effect of the verbal nature of the stimuli, as was specified by Ali and Cimino. Relatedly, Grunwald et al (1999) suggested that studies in which the perception of emotional words has been examined (i.e., lateralized paradigms, such as tachistoscopic techniques) have been less conclusive with regard to hemispheric specialization for emotion than have paradigms in which facial emotion or emotional prosody has been examined (for a review, see Borod, Bloom, & Haywood, 1998). The reason(s) for the inconclusiveness are poorly understood, although they may be attributable in part to similar weaknesses in experimental design, as described below.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors concluded that greater life experience may help raters image words, which would be consistent with the fact that older speakers use infrequent nouns more often than younger speakers, implying a larger vocabulary (Kave, Samuel-Enoch & Adiv, 2009). On the other hand, Grunwald et al (1999) found that older participants perceived lexical stimuli with significantly lower accuracy than younger participants. In addition, those authors found that women processed lexical stimuli more accurately than men.…”
Section: Relationship Of Imageability and Frequency To Rater Gender mentioning
confidence: 93%
“…The age groups did not differ signi®cantly from each other when analyses of variance (ANOVAs) were performed on these variables. This group of participants also served as the subjects in a study on lexical emotional perception (Grunwald et al, 1999).…”
Section: Participantsmentioning
confidence: 99%
“…Although there has been a fair amount of recent research on the neuropsychology of emotional language (for review, see Borod, Bloom, & Haywood, 1998), performance on measures of emotional language in healthy normal adults across the life span have only recently been directly examined (Grunwald et al, 1999). Grunwald et al (1999) examined the perception of lexical emotional stimuli as a function of age and found that older subjects perceived lexical stimuli less accurately than younger subjects in both emotional (E) and nonemotional (NE) conditions. In addition, lexical emotional expression was examined in these same subjects (Grunwald, 1995) using a measure of total output, and there were no changes with age.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation